PENGEMBANGAN PEMBELAJARAN DENGAN SISTEM KREDIT SEMESTER DI MTS NEGERI SUMBER BUNGUR PAMEKASAN - Muhlis, Achmad (STAIN PAMEKASAN, 2017)
Development of learning using Semester Credit System (SKS) is an innovative efforts undertaken by MTs Sumber Bungur Pamekasan which an effort to improve the quality of learning. This is done as an effort to present education service that is effective, efficient and maximum to a plurality of learners so that its potential can be explored properly, maximumly and fast, and allows the learners to obtain the opportunity to get treatment in accordance with learning capacity and Learning achievements that are achieved individually. This article is the result of research that tries to unravel in a whole on the development of learning with credit semester system at MTs Sumber Bungor Pamekasan.Â